TATHBIIQU THARIIQAH AL-QIRA`AH FII TA’LIIMI KITAABAH MUKHTASHAR JIDDAN FII AS-SHAF AT-TSAMIN BI MA’HAD AL-ISLAMIYYAH TANJUNG UBAR HASAN NAULI PANDANG BOLAK JULU PADANG LAWAS AS-SYIMAALIYYAH - Nur Alawiyah Samosir; Yunaldi (Program Studi Pendidikan Bahasa Arab, 2023)
A very brief book is a grammar book that is used in the eighth grade middle school of the Tanjung Ubar Hassan Noli Islamic Institute and in its teaching the teacher uses the method of reading. The objectives of this research are: To know how to apply the method of reading in teaching a very brief book and the difficulties that students face when teaching it. In this research using qualitative research. The result of this research indicates that the teacher who teaches in this class using the reading method method is of the type of common reading in teaching a very short book and teaches the teacher by reading aloud as well as intensive and analytical reading, but some of the students are more impressed and do not like or get excited when learning in the classroom